Pengaruh Kreativitas Siswa dan Full Day School Terhadap Prestasi Siswa dalam Pembelajaran PAI dan Budi Pekerti Kelas X di SMA Negeri 10 Kota Bengkulu - Ardianti Yunita Putri; husnul Bahri (UIN Fatmawati Sukarno Bengkulu, 2025)
This study aims to determine the effect of student creativity and the implementation of full day school on learning achievement in Islamic Religious Education and Character Building subjects at SMA Negeri 10 Kota Bengkulu. The background of this research is based on the low academic achievement of some students despite the application of the full day school system and varying levels of learning creativity. This research uses a quantitative approach with multiple regression analysis techniques. The results show that both student learning creativity and full day school system significantly influence the improvement of academic achievement. These findings are expected to serve as a basis for improving PAI learning quality and designing a more effective education system.